Diet and Pediatric Functional Gastrointestinal Disorders in Mediterranean Countries - Strisciuglio, Caterina; Cenni, Sabrina; Serra, Maria Rosaria; Dolce, Pasquale; Kolacek, Sanja; Sila, Sara; Trivic, Ivana; Bar Lev, Michal Rozenfeld; Shamir, Raanan; Kostovski, Aco; Papadopoulou, Alexandra; Roma, Eleftheria; et al. (MDPI AG, 2022)
Background: The increased intake of FODMAP (fermentable oligosaccharides, disaccharides, monosaccharides, and polyol) rich foods has been suggested as a possible trigger of functional gastrointestinal disorders (FGIDs). Despite the high FODMAP content, the Mediterranean diet (MD) appears to have beneficial effects on health. Our aim was to evaluate whether the prevalence of FGIDs in different Mediterranean countries may be influenced by FODMAP consumption and adherence to the MD. Methods: A school-based, cross-sectional, multicenter study was performed in six countries in the Mediterranean area: Croatia, Greece, Israel, Italy, Macedonia, and Serbia. Subjects 4-18 years were examined in relation to their eating habits and the presence of FGIDs, using Rome IV criteria, 3-day food diaries and Mediterranean Diet Quality Index in Children and Adolescents (KIDMED) questionnaires. Results: We enrolled 1972 subjects between 4 and 9 years old (Group A), and 2450 subjects between 10 and 18 years old (Group B). The overall prevalence of FGIDs was 16% in Group A and 26% in Group B. FODMAP intake was significantly different among countries for both age groups. In both groups, no significant association was found between FGIDs and FODMAPs. Adherence to the MD in all countries was intermediate, except for Serbia, where it was low. In both groups, we found a statistically significant association between FGIDs and the KIDMED score (Group A: OR = 0.83, p < 0.001; Group B: OR = 0.93, p = 0.005). Moreover, a significant association was found between the KIDMED score and functional constipation (Group A: OR = 0.89, p = 0.008; Group B: OR = 0.93, p = 0.010) and postprandial distress syndrome (Group A: OR = 0.86, p = 0.027; Group B: OR = 0.88, p = 0.004). Conclusions: Our data suggest that the prevalence of FGIDs in the Mediterranean area is not related to FODMAP consumption, whereas adherence to the MD seems to have a protective effect.